Pengembangan Video Pembelajaran Waffle Pisang Mas Dalam Mata Kuliah Pagelaran Cipta Karya Kuliner - Divani, Putu Tresya; Damiati, Damiati; Ekayani, Ida Ayu Putu Hemy (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to: (1) describe the Development stages of an instructional video on Waffle with banana (pisang mas) variation, and (2) assess the validity of the media based on expert validation and a small group trial. This research employs a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). Data were collected through questionnaires administered to experts and students during the limited trial phase. The research subjects consisted of three experts—material expert, media expert, and instructional Design expert—and ten students from the Vocational Culinary Arts Education Study Program. Data were analyzed using both qualitative and quantitative methods. The media was Developed through four stages of the 4D model: (1) Define, which involved needs analysis; (2) Design, which involved Designing the content and appearance of the media; (3) Develop, which involved product Development, expert validation, and small group testing; and (4) Disseminate, which involved distributing the instructional video via digital platforms such as YouTube. The validation results indicated a validity level of 95.85% from the material expert, 97.5% from the media expert, and 95.85% from the instructional Design expert, all categorized as “very valid.” The small group trial yielded a percentage of 92.27%, classified as “excellent.” These findings demonstrate that the Developed instructional video is suitable for use in teaching Fusion Dessert techniques.